2005
DOI: 10.1038/nature04028
|View full text |Cite
|
Sign up to set email alerts
|

GIBBERELLIN INSENSITIVE DWARF1 encodes a soluble receptor for gibberellin

Abstract: Gibberellins (GAs) are phytohormones that are essential for many developmental processes in plants. It has been postulated that plants have both membrane-bound and soluble GA receptors; however, no GA receptors have yet been identified. Here we report the isolation and characterization of a new GA-insensitive dwarf mutant of rice, gid1. The GID1 gene encodes an unknown protein with similarity to the hormone-sensitive lipases, and we observed preferential localization of a GID1-green fluorescent protein (GFP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
909
1
18

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,106 publications
(956 citation statements)
references
References 30 publications
28
909
1
18
Order By: Relevance
“…By contrast, several GA signaling components in rice (Oryza sativa) are encoded by single genes, making it a powerful system for studying this pathway. This is emphasized by a recent study by Ueguchi-Tanaka et al (2005) in which they identified the elusive GA receptor in rice. The identity of the GA receptors provides an important opportunity to dissect the GA signaling cascade in Arabidopsis (Nakajima et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, several GA signaling components in rice (Oryza sativa) are encoded by single genes, making it a powerful system for studying this pathway. This is emphasized by a recent study by Ueguchi-Tanaka et al (2005) in which they identified the elusive GA receptor in rice. The identity of the GA receptors provides an important opportunity to dissect the GA signaling cascade in Arabidopsis (Nakajima et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A major breakthrough in our understanding of the GA signaling cascade was the recent identification of GID1 as a soluble GA receptor in rice (Ueguchi-Tanaka et al, 2005). Genetic analysis of the gid1 mutants does not support the existence of other GA receptors in rice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous anatomical and in silico studies suggest that, similar to flowering plants, present-day bryophytes, including mosses, and lycophytes (lycopods) contain sporopollenin-containing outer walls on the surface of their spores and microspores [9][10][11] , and genes encoding CYP703 homologues have been detected in these genomes 12 . Curiously, however, one of the basal vascular plants, Selaginella, contains a functional GA perception system that is mediated by a GA receptor, GIBBERELLIN-INSENSITIVE DWARF1 (GID1), and suppressor proteins (DELLAs), whereas one of the basal land plants, Physcomitrella patens, does not contain this system [13][14][15][16] . These observations led us to speculate that the ancestral land plants developed sporopollenin-containing outer walls on their spores, which protected the spores from dryness and ultraviolet radiation on land, in association with CYP703-like enzymes, and that GA signalling pathway then evolved to control the development of the spore outer wall via the modulation of CYP703-like expressions during the evolution from mosses to lycopods.…”
mentioning
confidence: 99%
“…DELLA degradation initiates when GA binds to the soluble receptor GID1 (Ueguchi-Tanaka et al 2005;Griffiths et al 2006;Murase et al 2008). This event stimulates GID1-DELLA binding and recruitment of the E3 ubiquitin-ligase SLEEPY1 (Silverstone et al 2001;Willige et al 2007;Wang et al 2009).…”
Section: Resultsmentioning
confidence: 99%